2015
DOI: 10.1097/ico.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Structural Characteristics to Biomechanical Profile in Normal, Keratoconic, and Crosslinked Eyes

Abstract: CH and CRF are influenced by the corneal structure, with higher values noted in corneas with greater thickness and volume. Corneal biomechanical parameters progressively decrease as the severity of keratoconus increases. After collagen crosslinking, the relationship of the corneal curvature to the biomechanical profile is similar to normal eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
3
20
1
Order By: Relevance
“…Wong and Lam reported positive correlation both with CH and CRF [9]. In a recent study both CH and CRF were found to be correlated positively with CC and CV for the normal, keratoconic, and crosslinked eyes [22]. In this study, there are also positive correlations noted between CH, CRF, and CV.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Wong and Lam reported positive correlation both with CH and CRF [9]. In a recent study both CH and CRF were found to be correlated positively with CC and CV for the normal, keratoconic, and crosslinked eyes [22]. In this study, there are also positive correlations noted between CH, CRF, and CV.…”
Section: Discussionsupporting
confidence: 69%
“…This finding may suggest that posterior surface of the cornea may affect corneal biomechanical properties more compared to anterior surface in normal eyes. In a recent study, it has been shown that CH and CRF were negatively associated with K max value in keratoconic eyes, but this correlation did not exist for normal eyes [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In that aspect, in all patients, preoperative CCT, CTP and CV should be evaluated carefully. Unlike with our results, Viswanathan et al (31) determined a positive correlation of both CH and CRF with CCT in the normal, keratoconic and crosslinked eyes.…”
Section: Discussioncontrasting
confidence: 99%
“…The cornea is a soft tissue located in the outer layer of the eyeball. The transparent cornea provides 70% ocular refractive power [ 1 , 2 ]. Cornea can not only guarantee the external light to project to the retina directly, but also play an important role in maintaining the normal shape of the eyeball [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transparent cornea provides 70% ocular refractive power [ 1 , 2 ]. Cornea can not only guarantee the external light to project to the retina directly, but also play an important role in maintaining the normal shape of the eyeball [ 2 ]. The maintenance of normal corneal morphology has great significance in the prevention of myopia and keratoconus, and the changes of corneal morphology under different IOPs are closely related to corneal biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%